Study of far infrared cavity around a post AGB star under IRAS survey at galactic latitude -3° - A K Gautam; B Aryal (Bibechana, 2018)
A systematic search of dust structure in the far infrared (100 μm and 60 μm) under Infrared Astronomical Satellite (IRAS) survey was performed using Sky View virtual Observatory. In order to find the possible candidate of cavity structure not yet studied, we used SIMBAD database to locate discrete sources in the region. A new relatively symmetric spherical cavity like structure (size: 1.354 pc x 0.971 pc) at R.A.(J2000) =08h 03m 01.65s, Dec.(J2000) = -360 35' 47.9" was found at the distance of about 2800 pc. In this article, we have calculated  dust color temperature, dust mass  and size. We also studied the flux density variation and then calculated temperature and mass profile of the dust of p-AGB star using data reduction software Aladin2.5 and Aladin8.0. We have studied a cavity like structure centered at R.A.(J2000) = 08h 04m 07.21s, Dec.(J2000) = -370 11' 48.0". The dust color temperature is found to lie in the range 21.6 ± 0.09 K to 22.5 ± 0.05 K with an offset of 0.9 K. Such low off set suggests that the post AGB is in local thermodynamic equilibrium. The total mass of the dust in the cavity structure is found about 5.93 x 1025 Kg (0.00003M⊙)